Pengembangan Media Lagu dan Video Dalam Pembelajaran Terhadap Minat dan Hasil Belajar Mata Pelajaran IPA Kelas V SD Negeri Baturno Kabupaten Rembang - Titah Rahayu; Diah Kuniati; Nur Fajrie (Lembaga Pengembangan Kinerja Dosen, 2023)
Science (IPA) is one of the compulsory subjects taught in elementary school. The continued use of learning media to conduct science learning makes students bored and less enthusiastic about participating in learning. Media songs and educational videos can be used as an alternative to science learning. Educational songs and video media can motivate students to engage in science learning. The purpose of this study was to determine the effectiveness of media songs and video learning on interest and learning outcomes in science subjects among her 5th grade students at Baturno Public Primary School, Lembang Regency. The study design used was quasi-experimental with a non-equivalent control group design. The subject of this study was his 5th grade student at SD Negeri Baturno School in Lembang province. The sample for this study included all members of the population (saturated sample), 29 students in the experimental class and 28 students in the control class, for a total of 57 students. Data collection techniques used in this study include documentation, observation, and testing. As statistical analyses, Pearson product moments were used to test efficacy and Cronbach's alpha was used to test instrumental reliability. Lilliefors test to test data normality, Levene test to test homogeneity, independent-samples t-test, and sample t-test to test hypotheses.